2022
DOI: 10.1093/asj/sjac106
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Breast Implant Capsules and Breast Tissue: Findings from the Systemic Symptoms in Women–Biospecimen Analysis Study: Part 2

Abstract: Background Breast Implant Illness (BII), as described in recent medical literature and by social media, describes a range of symptoms in patients with breast implants for which there are no physical findings or laboratory results that explain their symptoms. The Aesthetic Surgery Education and Research Foundation (ASERF) Biospecimen study utilized a convergent design to prospectively study both qualitative systemic symptom data and quantitative heavy metals analysis of tissue obtained in surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Wixtrom et al noted a higher incidence of marijuana use in females self-reporting BII symptoms compared to controls as well as the fact that more females with BII symptoms smoked cigarettes than controls. 45 Cigarette smoking is known to be associated with increased rates of fatigue and depression 46 and is known to increase the risk of joint pain and cartilage loss within joint structures. 47 Marijuana use has been shown to produce “brain fog,” cognitive decline, anxiety, depression, fatigue, and hair loss with regular use.…”
Section: Adverse Effects Of Prescription Medications Taken For Chroni...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wixtrom et al noted a higher incidence of marijuana use in females self-reporting BII symptoms compared to controls as well as the fact that more females with BII symptoms smoked cigarettes than controls. 45 Cigarette smoking is known to be associated with increased rates of fatigue and depression 46 and is known to increase the risk of joint pain and cartilage loss within joint structures. 47 Marijuana use has been shown to produce “brain fog,” cognitive decline, anxiety, depression, fatigue, and hair loss with regular use.…”
Section: Adverse Effects Of Prescription Medications Taken For Chroni...mentioning
confidence: 99%
“…Gluten sensitivity and wheat allergy were found to be statistically higher in patients with self-reported BII symptoms compared to patients undergoing silicone implant exchange or mastopexy in a recent prospective study. 45 Nonceliac gluten sensitivity can present with many of the symptoms of autoimmune celiac disease, although the mechanism of this condition is unclear. 51 It is more common in females, typically in the fourth decade of life, with prevalence varying from 1% up to 13% of the general population.…”
Section: Adverse Effects Of Prescription Medications Taken For Chroni...mentioning
confidence: 99%
“…Implant capsules and breast tissue were analysed histologically and microbiologically and for heavy metals, and blood analyses were undertaken. Key findings included that the type of capsulectomy undertaken (intact total, total, or partial) did not alter symptom improvement10 heavy metal levels were not significantly higher or at toxic levels in the breast implant illness cohort11 and no significant differences in biospecimen analysis were seen 12. At one year, 88% of patients with symptoms showed at least partial improvement of systemic symptoms regardless of the type of capsulectomy performed 13…”
mentioning
confidence: 95%
“…Considerable progress has been made in research on breast implant illness, including a substantial series of publications 10111213. These studies looked prospectively at cohorts of women undergoing surgery with implants for breast implant illness related and unrelated reasons and women undergoing breast surgery without implants.…”
mentioning
confidence: 99%
“…The previously published Part 2 of the Systemic Symptoms Biospecimen Analysis Study showed that heavy metals contained within implant capsules are well below what are considered safe levels of exposure, and those that were higher in the symptomatic cohort could be attributed to lifestyle differences and potential environmental exposures and are unlikely to be a cause of symptoms. 1 …”
mentioning
confidence: 99%